The right tree for the right place: Use of centralized agroforestry species database system (Agroforestry Species Switchboard) by over 340,000 people worldwide supports decisions for context-sensitive agroforestry research, planting, and restoration initiatives - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
The Agroforestry Species Switchboard created by ICRAF is an online resource containing over 170,000 species and corresponding information across geographies. The Switchboard has been visited over 350,000 times by researchers and practitioners worldwide to support effective landscape restoration. The Switchboard has been recognized by the Agroforestry Network as a credible and useful resource for those seeking information on goods and services of desired species, including biology, value, and ecology to determine suitability for growing to support restoration initiatives.